2020
DOI: 10.1002/jcop.22393
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of ethnic‐racial socialization from family, school, neighborhood, and the Internet: Relations to adolescent outcomes

Abstract: Given that ecological models of development highlight the interacting influences of multiple environments, further research is needed that explores ethnic‐racial socialization from multiple contexts. The current study explores how families, schools, neighborhoods, and the Internet jointly impact academic outcomes, critical consciousness, and psychological well‐being in adolescents, both through socialization messages and experiences with racial discrimination. The research questions were: (a) What profiles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 101 publications
(137 reference statements)
4
51
2
Order By: Relevance
“…Recognizing that there is a robust difference in sleep on weekdays as compared to weekends (Roepke & Duffy, 2010;Vitale et al, 2015), this study also considered whether the impact of everyday discrimination on sleep/wake problems would differ by the day of the week. It is possible that adolescents had stronger, immediate responses to discriminatory incidents on weekdays coupled with stronger recovery (i.e., decrease in subsequent daytime dysfunction), because school is also a socializing forum in which adolescents obtain social support (Byrd & Ahn, 2020). On the other hand, adolescents may be less susceptible to discrimination on weekends yet experienced a lagged impact of discrimination (i.e., increase in subsequent daytime dysfunction).…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing that there is a robust difference in sleep on weekdays as compared to weekends (Roepke & Duffy, 2010;Vitale et al, 2015), this study also considered whether the impact of everyday discrimination on sleep/wake problems would differ by the day of the week. It is possible that adolescents had stronger, immediate responses to discriminatory incidents on weekdays coupled with stronger recovery (i.e., decrease in subsequent daytime dysfunction), because school is also a socializing forum in which adolescents obtain social support (Byrd & Ahn, 2020). On the other hand, adolescents may be less susceptible to discrimination on weekends yet experienced a lagged impact of discrimination (i.e., increase in subsequent daytime dysfunction).…”
Section: Discussionmentioning
confidence: 99%
“…The authors were also interested in how adolescents in these profiles differed on key outcomes such as dimensions of critical consciousness and civic engagement. The authors found that the High Discrimination profile, characterized by high levels of discrimination across home, school, neighborhood, and online contexts, along with frequent ethnic-racial socialization messages (including preparation for bias), reported the greatest interpersonal, communal, and political engagement of all profiles (Byrd & Ahn, 2020). Taken together, youth participation in CCE is likely motivated by youths' understanding of racial inequality, which is shaped, in part, by preparation for bias messages provided by parents as well as their experiences of racial discrimination and racial centrality (Anyiwo et al, 2018).…”
Section: Predictors Of Critical Civic Engagementmentioning
confidence: 99%
“…For instance, racial discrimination heightens the importance youth place on being Black as part of their identity (i.e., centrality or pride in being Black; Butler‐Barnes et al., 2019), contributes to lower positive affect about being Black (low private regard), contributes to greater belief that others think negatively about Black people (low public regard; Seaton et al., 2009), and disrupts normative racial identity developmental processes such as exploring and committing to one’s racial identity (Douglass & Umaña‐Taylor, 2017). Regarding racial oppression and social cognition, in a study utilizing a person‐centered approach to multiple contexts of socialization, Black adolescents who had the highest scores on receiving messages about race and experiencing racial discrimination demonstrated the greatest social cognition about social inequality (i.e., critical reflection; Byrd & Ahn, 2020). Finally, in a study among high achieving Black high school girls, findings demonstrated that the experience of navigating issues of diversity within school was associated with Black adolescent girls’ demonstration of autonomy in the assertion of their own racial ideologies and expressions of their Blackness in ways that were accommodating instead of assimilating (Marsh, 2013).…”
Section: Emotional Development Among Black Adolescentsmentioning
confidence: 99%